Cardioprotective effect of crocin in patients with breast cancer receiving anthracycline-based chemotherapy: A randomized, double-blind, placebo-controlled study - Xinye Li; Xin Su; Wanping Liang; Li Wang; Chao Yuan; Juping Xu; Yijun Zhang; Yan Liu; Ning Ma; Fan Yang; Yiyuan Yang; Liyuan Tao; et al. (Pharmacological Research)
Anthracycline chemotherapy leads to cardiotoxicity in patients with breast cancer. We performed a double-blind randomized controlled trial to assess the efficacy of crocin (crocin tablets) in reducing anthracycline-induced cardiotoxicity in breast cancer patients. Eligible patients were randomly assigned to receive either treatment with crocin tablets or placebo for 6 months. Primary efficacy outcome was the proportion of patients with a drop in left ventricular ejection fraction (LVEF) of at least 10 % from baseline until 6 months. We randomized 200 patients; 7 of them had no valid randomization as the change in chemotherapy scheme. A total of 193 eligible participants (mean [SD] age, 50.9 [9.6] years; all women) were randomly assigned to receive crocin tablets or placebo. The incidence of the primary efficacy outcome was 7.2 % (7/97) in the crocin group and 17.7 % (17/96) in the placebo group (P = 0.027). At 6 months, there were significant differences in the mean change of N-terminal pro–brain natriuretic peptide (NT-pro BNP) between the groups (3.06 [-25.18–6.95] vs. 3.06 [-4.85–24.98] pg/ml; P = 0.017). The changes in heart rate from baseline to 6 months showed a significant difference as the mean difference of −4.00 (95 %CI, −6.95 to −1.05) bpm (P = 0.008). Conclusively, among patients with breast cancer treated with anthracycline-based chemotherapy, crocin tablets reduced the incidence of LVEF reduction. This finding indicated that crocin tablets might be a safe and effective therapy to prevent the cardiotoxicity in this population. (Chictr.org.cn, ID Number: ChiCTR2000041134).